Metal‐Dependent Support Effects of Oxyhydride‐Supported Ru, Fe, Co Catalysts for Ammonia Synthesis. Issue 36 (8th November 2018) - Tang, Ya; Kobayashi, Yoji; Masuda, Naoya; Uchida, Yoshinori; Okamoto, Hiroki; Kageyama, Toki; Hosokawa, Saburo; Loyer, François; Mitsuhara, Kei; Yamanaka, Keisuke; Tamenori, Yusuke; Tassel, Cédric; et al.
Abstract: Ammonia is an attractive energy carrier for the hydrogen economy, given its high hydrogen density and ease of liquefaction. A titanate oxyhydride has recently been demonstrated that can catalyze ammonia synthesis without Ru or Fe metal, despite titanium being regarded as an inert element. Here, the synthesis activity of ammonia is examined when Ru, Fe, and Co particles are supported onto the oxyhydride BaTiO2.5 H0.5 . The activity of BaTiO2.5 H0.5 as support is significantly higher than BaTiO3 . For example, the activity for Fe and Co increases by a factor of 70–400, making them more active than Ru/MgO, one conventional Ru catalyst. In terms of mechanism, for Ru, H/D isotope studies show participation of lattice hydride in the catalytic cycle, while kinetic analysis shows reduced H2 poisoning probably due to spillover. For Fe (and Co), the presence of hydride results in significantly lower activation energy and N2 reaction order, likely due to strong electron donation from the oxyhydride. This metal‐dependent support effect is further verified by N2 isotopic exchange experiments. These perovskite‐type oxyhydrides can be easily modified in terms of A ‐ and B ‐site ( A = Ba, B = Ti); the high potential for compositional variation and morphologies will expand the search for efficient catalysts for ammonia synthesis. Abstract : The addition of hydride to an oxide support enhances the ammonia synthesis activity of Ru, Fe, Co‐based catalysts by orders of magnitude. The results provide convincing evidence of lattice hydride participating in the catalytic cycle, and the measured kinetic parameters/isotopic exchange experiments describe a novel metal‐dependent support effect from the oxyhydride supports.